The human eccrine sweat gland: Structure, function and disorders - Douglas Bovell (19772802) (2015)
The ability to thermoregulate is a key component in allowing humans to live and work in a variety of torrid environments. A key thermoregulatory component is the role the skin plays in dissipating heat, through vasodilation of skin blood vessels and its critical role in the secretion of sweat. The role of sweating has for a long time been regarded primarily as the main function of the human eccrine sweat gland, although it has been known for a considerable length of time that sweat, produced in response to heat and exercise, was more than just a salt solution and contained a variety of other substances in addition to electrolytes. Recent studies have shown that there is more to the human eccrine gland, such as manufacturing and releasing compounds that contribute to the defensive barrier of the skin, as well as stem cells present in the gland, having a role to play re-epithelialization of the skin in response to wound healing. Disorders of sweat glands and the resultant conditions, most often relate to defects in the secretion of sweat and its release on to the skin surface. This review concentrates on the processes that enable the production of human sweat. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.5